Preparation and evaluation of identifiable quick response (QR)-coded orodispersible films using 3D printer with directly feeding nozzle - Oh, Byung Cheol; Jin, Gang; Park, Chulhun; Park, Jun Bom; Lee, Beom Jin (International Journal of Pharmaceutics, 2020)
3D-printing technology is growing in importance due to increased availability and a wider range of applications. Here, we prepared and evaluated a hot melt pneumatic (HMP) 3D-printed QR (Quick Response)-coded orodispersible film (QRODF) containing a poorly water-soluble aripiprazole (ARP). Moreover, QRODF was formulated to evaluate the extrusion process and characterize physicochemical properties of drug-loaded films. QRODF was designed with a 30-mm length/width and 0.3-mm thickness by varying QRODF formulations with different polyethylene oxide 100,000(PEO)/poloxamer 188(POX188) ratios and then optimized for extrusion accessibility and film-forming capability. The optimal QRODF formulation was further controlled by ARP and citric acid addition (pH control) for salivary applicability and dissolution rate. Physicochemical evaluation of QRODF was performed by scanning electron microscopy, differential scanning calorimetry, and powder X-ray diffraction. Dissolution studies were performed in buffer media (pH 1.2) following USP Apparatus type II method. Drug-loaded QRODF was scannable using a smartphone. Drug release from QRODF rapidly reached over 95% and was dependent on polymer/poloxamer ratios. By optimizing PEO/POX/drug ratio, the morphology and physical properties of the oral film were changed. Furthermore, disintegration and dissolution rates of ARP-loaded QRODF were successfully established in a controlled manner.
Keywords: Aripiprazole; Calorimetry, Differential Scanning; Drug Liberation; Electronic Data Processing; Excipients; Hydrogen-Ion Concentration; Microscopy, Electron, Scanning; Poloxamer; Polyethylene Glycols; Printing, Three-Dimensional; Saliva; Smartphone; Solubility; Technology, Pharmaceutical; Tensile Strength; X-Ray Diffraction; 3D printer with directly feeding nozzle; Aripiprazole; Enhanced dissolution; Orodispersible film; QR code; Rapid disintegration